"Very simple. I just don't lie": The role of honesty in Black lesbian K-12 teachers' experiences in the U.S. Southeast. Issue 4 (2nd October 2017) - Ford, Jillian Carter
ABSTRACT: I conducted semi-structured interviews with eight self-identified Black lesbian classroom teachers. Seven participants taught in three districts in the same large metropolitan area in the U.S. Southeast; one participant taught in a smaller city in a bordering state. In response to the vague prompt to describe the intersections between their sexuality and their schooling experiences as a teacher, every participant spoke explicitly about her unwillingness to lie about her sexuality if asked. In this article, I argue that honesty is a critical component of Black women's experiences, the necessity of which can be tied to womanism.